THE INFLUENCE OF WORKLOAD AND WORKING ENVIRONMENT ON CYBERLOAFING BEHAVIOR MEDIATED BY JOB STRESS IN 74 AND 58 STATE PRIMARY SCHOOL TEACHERS IN BENGKULU CITY - Astiezah, Rofifah; Muafi, Muafi (Universitas Muhammadiyah Tangerang, 2024)
Respondents to this study are provided with questionnaires as part of a quantitative methodology. Eighty teachers from Bengkulu City's State Elementary Schools 74 and 58 participated in this study. The data in this study are analyzed using the Partial Least Square (PLS) with Structural Equation Model (SEM). The results of this study showed that: (1) the work environment influences work stress in a significant and negative way; (2) job stress influences work stress in a significant and positive way; (3) job stress has the ability to mediate the relationship between workload and cyberloafing behavior (4) job stress has the ability to moderate the impact of the workplace on the behavior of cyberloafing; and (5) job stress influences cyberloafing behavior in a positive and significant way. The managerial implications in this research show that there is a need for optimization in maintaining workload and always striving for a conducive work environment. This will support teachers at SD Negeri 74 and SD Negeri 58, Bengkulu City in increasing their work productivity. Having a conducive work environment and not excessive workload on teachers can reduce work stress and reduce cyberloafing behavior in teachers.